2000
DOI: 10.1002/1096-9861(20001009)426:1<13::aid-cne2>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrastructure of physiologically identified premotoneuron terminals in the trigeminal motor nucleus in the cat

Abstract: Little is known about the ultrastructure of synaptic boutons contacting trigeminal motoneurons. To address this issue, physiologically identified premotor neurons (n = 5) in the rostrodorsomedial part of the oral nucleus (Vo.r) were labeled by intracellular injections of horseradish peroxidase (HRP) in cats. The ultrastructure of 182 serially sectioned axon terminals from the five neurons was both qualitatively and quantitatively analyzed. In addition, the effects of the glycine antagonist strychnine, GABA(A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Thus far, an anatomical pathway that could transmit to Mo5 signals from the VN or the adjacent prepositus hypoglossi (PH), which also receives direct and multisynaptic inputs from the vestibular endorgans (Kevetter et al 2004;McCrea and Baker 1985;McCrea et al 1979), has not been clearly defined. Many studies have been performed, using a variety of different methods and animals species, to identify the afferent projections to Mo5 (Vornov and Sutin 1983;Travers and Norgren 1983;Mizuno et al 1983;Li et al 1995;Fay and Norgren 1997;Kolta et al 2000;Shigenaga et al 2000;Westberg et al 2001;Inoue et al 2002). However, none of these studies demonstrated the existence of projections from the VN to trigeminal motoneurons, and only sparse projections from PH to Mo5 were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, an anatomical pathway that could transmit to Mo5 signals from the VN or the adjacent prepositus hypoglossi (PH), which also receives direct and multisynaptic inputs from the vestibular endorgans (Kevetter et al 2004;McCrea and Baker 1985;McCrea et al 1979), has not been clearly defined. Many studies have been performed, using a variety of different methods and animals species, to identify the afferent projections to Mo5 (Vornov and Sutin 1983;Travers and Norgren 1983;Mizuno et al 1983;Li et al 1995;Fay and Norgren 1997;Kolta et al 2000;Shigenaga et al 2000;Westberg et al 2001;Inoue et al 2002). However, none of these studies demonstrated the existence of projections from the VN to trigeminal motoneurons, and only sparse projections from PH to Mo5 were observed.…”
Section: Introductionmentioning
confidence: 99%
“…From previous studies, the rostro‐dorsomedial part of the trigeminal nucleus (Vor) receiving the trigeminal primary afferents contained neurons terminating in the trigeminal as well as facial motor nucleus 24,25 . Other studies also showed that Vor neurons made synaptic contact with either jaw closing or jaw opening motoneurons 26,27 . Yoshida et al 28 found that Vor neurons with the mechanoreceptive field in oral tissues bilaterally innervated jaw‐opening or jaw‐closing motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Other studies also showed that Vor neurons made synaptic contact with either jaw closing or jaw opening motoneurons. 26,27 Yoshida et al 28 found that Vor neurons with the mechanoreceptive field in oral tissues bilaterally innervated jaw-opening or jaw-closing motoneurons. This raises the question of how exactly the post-Dig reflex response is evoked.…”
Section: Discussionmentioning
confidence: 99%
“…This arrangement is analogous to the primary somatosensory afferents that show more frequent contact with the soma/proximal dendrite compartment of the postsynaptic neurons in the trigeminal oral nucleus, which controls reflexive oral motor behavior, than in the trigeminal principal nucleus, which is involved in the somatosensory perception ( Bae et al, 2000 ). Axon terminals of premotor neurons also very frequently form synapses with the soma/proximal dendrite compartment of the postsynaptic neurons in the trigeminal motor nucleus ( Shigenaga et al, 2000 ; Paik et al, 2009 ). All of the above suggests that the terminals of excitatory neurons that mediate motor reflexes may exert a stronger influence on the activity of the postsynaptic neurons than those that mediate sensory perception.…”
Section: Discussionmentioning
confidence: 99%